2019
DOI: 10.1016/j.heliyon.2019.e02085
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of variability and change in rainfall on gender of farmers in Anambra, Southeast Nigeria

Abstract: Men and women farmers experience different impacts of climate variability and change (CVC). Research on the differentiated impacts of variability and change in rainfall on gender is limited in the study area. This study examined perceptions and experience of men and women farmers on the impacts of CVC, using climate data and farmers' perception from a gender perspective. It examined the effect of CVC on annual and seasonal rainfall, number of rain days, onset and cessation of rainfall; perceived impacts of CVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…We aimed to collect pre-exercise blood samples before the heavy rainfall season in June. In Nigeria, rainfall peaks in June [ 83 ] and is associated with increased opportunistic infections that influence CD4 count. After each sample was collected, we examined the tube for integrity before transporting to the testing center.…”
Section: Methodsmentioning
confidence: 99%
“…We aimed to collect pre-exercise blood samples before the heavy rainfall season in June. In Nigeria, rainfall peaks in June [ 83 ] and is associated with increased opportunistic infections that influence CD4 count. After each sample was collected, we examined the tube for integrity before transporting to the testing center.…”
Section: Methodsmentioning
confidence: 99%
“…Domestic tasks which rural women mostly combine with farm work made it harder for them to engage in non-farm activities. In the works of Nnadi et al [40] on climate variability impacts among rural residents in Anambra state as well, women were also more negatively impacted than men. Among women traders in Bayelsa state, flooding also adversely affected their livelihood patterns [41].…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, the aforementioned study did not report increased demands on women to find employment, as observed in the present study. Evidence from Nigeria has illustrated how climate variability, specifically inconsistent rainfall and droughts, catalyzes male out-migration from rural agricultural communities to urban areas; in the process, women absorb a greater share of domestic responsibilities and workloads but with fewer resources than men, like farming inputs and deeds to land [ 39 ].…”
Section: Discussionmentioning
confidence: 99%